1989
DOI: 10.1089/dna.1.1989.8.377
|View full text |Cite
|
Sign up to set email alerts
|

The Human Genome Contains Hundreds of Genes Coding for Finger Proteins of the Krüppel Type

Abstract: Our aim was to identify new human proteins with potential DNA binding activity, related to the Krüppel protein which regulates Drosophila segmentation. We screened a human placenta cDNA library and a human genomic DNA library with a synthetic oligonucleotide probe corresponding to the H/C link region that connects finger loops in the multifingered Krüppel protein. We found more than 100 different mRNAs encoding Krüppel multifingered proteins in the human placenta. In the whole human genome, the number of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
109
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(111 citation statements)
references
References 43 publications
1
109
0
1
Order By: Relevance
“…In humans, proteins containing zinc finger motifs (10) represent one of the largest known gene families (11). It has been estimated that up to 1% of all genes in the human genome may encode proteins with zinc finger domains (12).…”
mentioning
confidence: 99%
“…In humans, proteins containing zinc finger motifs (10) represent one of the largest known gene families (11). It has been estimated that up to 1% of all genes in the human genome may encode proteins with zinc finger domains (12).…”
mentioning
confidence: 99%
“…A widespread transcriptional repressor motif is the KRAB-A domain (3)(4)(5)(6), which is found in approximately one-third of all zinc finger proteins of the Cys 2 His 2 class (7,8). Zinc finger proteins of the Cys 2 His 2 class represent one of the largest protein families known; the mammalian genome contains several hundred genes coding for such proteins (9), and the KRAB-A domain therefore represents a very important paradigm of transcriptional repression. Experiments from several laboratories have shown that the KRAB-A domain represses transcription both upstream and downstream of a target gene and is able to do so from a distance (5,10).…”
mentioning
confidence: 99%
“…The C 2 H 2 Zinc fingers have been shown to bind DNA in a sequence-specific manner, and the KRAB domain represses DNA transcription (15,36,37). However, only a few in vivo targets have been identified for these proteins.…”
Section: Disscussionmentioning
confidence: 99%